On a stability of the North Atlantic thermohaline circulation - Polonsky, A.B.; Bazyura, E.A.; Sannikov, V. F. (Reports of the National Academy of Sciences of Ukraine, 2014)
Features of the North Atlantic thermohaline circulation response to instantaneous, periodic, and stochastic forces within the four-box model are studied. Typical variations of the boundary conditions are estimated by the modern data sets. It is shown that the thermohaline circulation in the modern climate epoch is characterized by a quasi periodic stable oscillation regime. The thermohaline catastrophe (dramatic weakening of the meridional ocean circulation) is improbable.